DETECTION OF BACTERIOCIN (STAPHYLOCOCCIN) ACTIVITY OF STAPHYLOCOCCUS AUREUS ISOLATES IN CHICKENS. - Al-Jobori, ASMAA H.A. (The Iraqi Journal of Veterinary Medicine, 2021)
Twenty isolates of Staphylococcus aureus were examined, fourteen from them showed staphylococcin activity while six isolates were not producers. The staphylococcin activity of potential producer isolates was increased if CaCl2 was incorporated in the medium and if the cultures were induced with ultra violet radiation.